The influence of transformational leadership and emotional intelligence on job performance in the Malaysian hotel industry - Muzalifah Monil
Job performance of hotel frontline employees are becoming more important as they provide a benchmark for the hotel industry to excel in terms of the quality of services provided. Past studies have confirmed two major problems face by the hotel industry; long working hours and low wage, causing high turnover and absenteeism. Moreover, turnover rate is highest in the Malaysian hotel industry as reported by the Ministry of Human Resources. This research aims to examine the influence of transformational leadership and emotional intelligence on job performance. In addition, the study examines how organizational commitment and communication satisfaction mediate the effects of transformational leadership and emotional intelligence on job performance. A structured questionnaire consisting of job performance (18 items), emotional intelligence (21 items), transformational leadership (15 items), organizational commitment (14 items) and communication satisfaction (17 items) is adapted from previous researches. Stratified sample of 356 respondents from the frontline employees is chosen from selected hotels in Malaysia. Data are analyzed by using Advance Statistical Package for Social Sciences (SPSS) with macro and syntax methods. Various statistical tests are conducted to analyze the hypothesized relationship among the dependent, independent and mediating variables. The results indicate that transformational leadership, emotional intelligence and communication satisfaction significantly influence job performance. Tills shows that the three variables are important to be considered in evaluating the performance of frontline hotel employees. However, organizational commitment is found to be insignificant in influencing job performance. This contradicts to the Individual Job Performance Theory. This suggests that organizational commitment may be considered less important in evaluating the performance of frontline employees. The results from the study can assist managers to evaluate the performance of frontline employees in the Malaysian hotel industry.